EMPOWERING COASTAL COMMUNITIES IN KEPUTIH: WASTE MANAGEMENT AND CRAFTING FOR ECONOMIC EMPOWERMENT - Diyanah, Khuliyah Candraning; Pawitra, Aditya Sukma; Putri, Nuzulul Kusuma; Adriyani, Retno; Prasasti, Corie Indria; Sudarmaji, Sudarmaji; Mukono, Jojok; Keman, Soedjajadi; Sulistyorini, Lilis; Azizah, R.; Lusno, Muhammad; Lestari, Kusuma; Arfiani, Novi; Yudhastuti, Ririh; Husnina, Zida; Wardani, Ratnaningtyas; Rohmah, Shofiyatur; Alif, Achmad; Muhashonah, Izzuki (Universitas Airlangga, 2025)
Waste is a classic problem for developing countries like Indonesia. Coastal areas are one of the areas that most vulnerable to environmental problems, especially those related to plastic waste. This community service activity aims to increase community knowledge about the importance of waste management and encourage them to turn waste into handicraft products that have economic value. This community service activity is in partnership with the community in the Keputih coastal area and local community leaders in RT VII RW VIII Keputih. The method used is to provide counseling, training and assistance to the community. Evaluation of activities is carried out by assessing: 1) knowledge about waste (inorganic and organic that is difficult to decompose) through pre-test and post-test regarding educational materials, 2) assessment of the ability to practice waste management (crafting) and 3) Impact of activities is carried out by reviewing Has waste management been implemented from households to TPS? The education and assistance on waste management, including sorting and making handicrafts from waste, has been successful with 3 indicators achieved, namely the presence of the community in counseling (80%), 65% of the target community has increased their knowledge, and 75% of the target community has sorted waste and made crafts from plastic waste. It is hoped that community service activities can be sustainable, such as providing education to target communities regarding how to sell handicrafts made from waste, and collaborating with other parties that can improve the branding of handicraft products.